Sifat Mekanik Beton Mutu Tinggi Dengan Kombinasi Slag Nikel Dan Slag Baja - Yoel Lian Tiranda; Herman Parung; Desi Sandy (Paulus Civil Engineering Journal, 2021)
This study is intended to determine the composition of the concrete mixture, the strength of the concrete and the ratio of the strength of the concrete with the combination of nickel slag and steel slag as a substitute for fine aggregate and coarse aggregate. The percentage of use of nickel slag waste of 50% as a substitute for fine aggregate and steel slag waste varies from 0%, 15%, and 30% as a substitute for coarse aggregate in high quality concrete mixtures (f'c = 42 MPa). In this study, the mix design uses the SNI 03-2834-200 method. The specimens used were 36 cylinders with a diameter of 15 centimeters and a height of 30 centimeters and 9 beams with a size of 15x15x60. Tests made in 7 days, 21 days, and 28 days age variations. Based on the mechanical properties of the average concrete using steel slag waste as a substitution at 30% variation, the greatest results were 45.27 MPa, 4.91 MPa and 5.09 MPa respectively for compressive strength, split tensile strength and concrete flexural strength.